Impact of Green Marketing Stimuli on Green Purchasing Intention of Sri Lankan Consumers - Perera, W. V. T.; Gayathree, D. A. G. P. K. (Department of Marketing Management, Faculty of Commerce and Management Studies, University of Kelaniya Sri Lanka, 2021)
Sri Lanka is an Asian developing country and majority of citizens are environmental concerned because of the culture. The number of consumers who consider environmental friendliness increases over time in Sri Lanka and with this trend organization have been adapting green marketing strategies. Thus, this study examined the Impact of Green Marketing Stimuli on Green Purchasing Intention of the Sri Lankan Consumers. The data collected from 385 consumers who resides in the Western province and the respondents were selected using convenience sampling method. Self-administered questionnaire was distributed among the respondents. The data analyzed using SPSS version 26. The findings demonstrated a significant impact of eco labeling, eco packaging, environmental concern, and government role to green purchase intention. The results further indicated that customer income moderated the relationship between green marketing stimuli and green purchase intention.
Keywords: Consumer Income, Eco Labelling, Eco Packaging, Environmental Concern and Government Role